Archival silences: Missing, lost and, uncreated archives - CENGİZ, EMİNE (My University, 2022)
This paper aims to review the book titled “Archival silences: missing, lost and, uncreated archives” edited by Michael Moss and David Thomas. Michael Moss and David Thomas are leading and valuable scholars in archival science. This book addresses fundamental issues of access to the records in countries. It is directed at those with a concern for social justice, particularly scholars and students of archival studies, history, sociology, international relations, international law, business administration and information science. The book was published in its original language in 2021.
Keywords: Sosyal ve Beşeri Bilimler; Bilgi ve Belge Yönetimi; Social Sciences and Humanities; Management of Information and Documents; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; BİLGİ BİLİMİ VE KÜTÜPHANE BİLİMİ; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; INFORMATION SCIENCE & LIBRARY SCIENCE; Bilgi Sistemleri ve Yönetimi; Kütüphane ve Bilgi Bilimleri; Sosyal Bilimler ve Beşeri Bilimler; Information Systems and Management; Library and Information Sciences; Social Sciences & Humanities